Translating the Symbolic Hunting Series in Golding’s Lord Of The Flies from English into Arabic: A Relevance-Theoretic Perspective - Al-Zu’bi, Khaled; Abdul Ghani, Aniswal (Australian International Academic Centre (AIAC), 2017)
This study comes as a response to the need for comparative assessment and evaluation studies of stylistic differences between English and Arabic in the field of literary translation in the Arab World. The main objective of this explanatory, analytical and comparative study was to investigate the translation of symbolism in William Golding’s Lord Of The Flies (LOTF). The rich cultural connotations behind the employment of symbols in literary works constitute a great challenge to the literary translator. There is a need to ascertain the appropriateness of the translated symbols in the Arabic versions of LOTF. Two Arabic translations, Darweesh and Qaseh (2004) and Hamid (2002), are compared in terms of conveying the original symbolic style of the hunting series in LOTF. This study attempts to provide a relevance-theoretic account for the translation of symbols between English and Arabic. Relevance Theory (RT), as a communication theory which builds on a pragmatics, provides a way out of the traditional emphasis on the concept of the translation equivalence. It concentrates on the contextual environment of both the source language (SL) and the target language (TL) in achieving successful communication.